EKO 9 Triennial of Art and Environment - Kyprianidou, Efi (My University, 2024)
From folktales and the origins of modern horror in literature and film to contemporary art forms, the horror genre has always possessed the potential to address human and societal fears. With the exhibition Eyes in the Stone, we give power to the primary emotion of fear to jolt us from our numbness to seemingly failing warnings of science. The artists in the exhibition respond in form and narrative to the threatening atmosphere in nature and culture. In the new venue of the EKO Triennial – the old sanatorium of Dr Mirko Černić in the centre of Maribor – we present artworks which through use of shock, a sense of dread, disquiet and despondency, as well as critical reflection, offer a chance at catharsis in the face of environmental collapse.
EYES IN THE STONE